Performance Evaluation of DSSC as Distributed Power Flow Controller in Transmission Network - R. Gaigowal, S.; M. Renge, M. (International Journal of Engineering and Technology, 2018)
Converter based FACTS controllers provides power flow control through transmission line. But due to its high cost and low reliability issues, it is not widespread installed over worldwide. Distributed FACTS provides a compensation in cost effective and reliable way in interconnected power system. Distributed static series compensator (DSSC) is one of the member of distributed FACTS family. In this paper, DSSC is demonstrated as distributed power flow controller to realize active power flow through the line. DSSC is a low power, low cost, light weight single phase inverter and it can be directly attached on the existing line with the help of single turn transformer. It injects a very small voltage in the line in quadrature with the line current which gives a negligible change in active power. Multiple devices are needed to provide on the line to get noticeable change in active power. In this work, particle swarm optimization is implemented to find optimum reactance emulated by DSSC to provide secured power system operation and control. Objective is formulated such that no line would carry line current above its thermal limits. Similarly, reactive power generation is minimized using DSSC devices considering main constraint that power flow through each line would be within its acceptable range. Voltage stability is also analyzed on DSSC compensated system. DSSC compensation in capacitive mode of operation is demonstrated for loading margin enhancement. Furthermore, fault current limiting using DSSC devices is demonstrated. MATLAB results validate the work.Â Â